IMPLEMENTASI PROGRAM CORPORATE SOCIAL RESPONSIBILITY DALAM PENYELENGGARAAN KESEJAHTERAAN MASYARAKAT - Iswiyati Rahayu ' (JIANA ( Jurnal Ilmu Administrasi Negara ), 2014)
Implementation of Corporate Social Responsibility Program for the Operationof Society Welfare. This study aims to determine the implementation of Corporate SocialResponsibility (CSR) and its impact on the welfare of society. This research uses descriptivequalitative approach to generate data and information that reliable and valid. Techniques of datacollection using interviews, observation and discussion of data sources is key informants takenwith snowball sampling method of the enterprise, government and society. Data were analyzedusing the interactive method. The results showed that the Program Implementation of CorporateSocial Responsibility (CSR) is not implemented optimally. Still found problems in economicdevelopment, land acquisition and environment that led to the conflict between the company,government and society.Keywords: program implementation, social responsibility, community welfare, conflict.